The mediating effect of study habits between parental involvement and algebraic problem-solving achievement - Ali, Imdad; Das, Samiran (International Journal of Evaluation and Research in Education (IJERE), 2025)
Algebra is the major branch of mathematics that deals with numbers, and symbols are mostly used in problem-solving. Students often struggle to learn mathematics due to the difficulties of solving algebraic problems at the secondary level. Several factors affect student problem-solving achievement (PSA). The present study aims to examine the mediating effect of study habits (SH) in the relationship between parental involvement (PI) and algebraic PSA. For this purpose, a study habits scale and a parental involvement scale are used, and a problem-solving test is done for algebraic problem-solving. In this correlational study, Baron and Kenny’s series of regression models is used to test the mediating effect of SH. The findings revealed that that PI, SH and algebraic PSA are positively correlated. Also, it is confirmed that SH mediates the relationship between PI and algebraic PSA because there is no longer any significant effect of PI on PSA after SH is included in the model. It is recommended that students’ problem-solving skills be developed through their better study habits. Increasing parental support may promote students better SH, which in turn better achievement in problem-solving. Parents and teachers should monitor and encourage students’ study habits for better performance in problem-solving and mathematics as a whole.